2008
DOI: 10.1111/j.1471-6712.2007.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of the first year as father

Abstract: To master fatherhood maintenance of integrity and possibility to develop an independent relationship with the child is important. Fathers are invited to participate in postnatal childbirth education but the activities address women's needs and it is doubtful if the fathers benefit from participation. Though fathers entered the delivery room some decades ago, as a support to the woman, health personnel of today must be aware of fathers' own needs and the impact gender aspects have on their professional support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
168
0
25

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(204 citation statements)
references
References 35 publications
11
168
0
25
Order By: Relevance
“…The limited time and often lacking energy created a focus on acknowledging each other through every day life and both previous research and this study confirm a new form of togetherness to evolve between the partners after having a child (Premberg et al 2008).…”
Section: Discussionsupporting
confidence: 75%
“…The limited time and often lacking energy created a focus on acknowledging each other through every day life and both previous research and this study confirm a new form of togetherness to evolve between the partners after having a child (Premberg et al 2008).…”
Section: Discussionsupporting
confidence: 75%
“…Passear e demonstrar afeto também foram interações citadas pelos pais como modo de haver trocas com o filho, que nesta fase, se apresenta mais responsivo às interações. A atividade de brincar do pai tende a ser considerada mais ativa e intensa que a materna mesmo no primeiro ano de vida (Premberg, Hellström, & Berg, 2008), embora, no presente estudo, as brincadeiras pareceram ser menos ativas e intensas, como brincar de boneca e até passear no colo ou de carrinho. Além disso, segundo Lindsey, Cremeens e Caldera (2010), os pais vocalizam mais com o bebê nessas interações, quando comparadas com momentos de cuidado do bebê.…”
Section: Discussionunclassified
“…There is some evidence that fathers also experience changes in sleep from the prenatal to the postpartum period. In a qualitative study, first-time fathers reported that all daily activities center around the infant's caretaking needs and sleeping times [58]. Furthermore, the sleep time of first-time fathers was significantly lower during the early postpartum period when compared to their sleep time assessed when their partners were at 23 weeks gestation [59].…”
Section: Postpartum Paternal Sleepmentioning
confidence: 99%